Genotype–Phenotype Correlations for Putative Haploinsufficient Genes in Deletions of 6q26-q27: Report of Eight Patients and Review of Literature - Xie, Xiaolei; Chai, Hongyan; DiAdamo, Autumn; Grommisch, Brittany; Wen, Jiadi; Zhang, Hui; Li, Peining (Global Medical Genetics, 2022)
Background Cytogenomic analyses have been used to detect pathogenic copy number variants. Patients with deletions at 6q26-q27 present variable clinical features. We reported clinical and cytogenomic findings of eight unrelated patients with a deletion of 6q26-q27. A systematic review of the literature found 28 patients with a deletion of 6q26-q27 from 2010 to 2020.Results For these 36 patients, the sex ratio showed equal occurrence between males and females; 29 patients (81%) had a terminal deletion and seven patients (19%) had a proximal or distal interstitial deletion. Of the 22 patients with parental studies, deletions of de novo, maternal, paternal, and bi-parental inheritance accounted for 64, 18, 14, and 4% of patients, respectively. The most common clinical findings were brain abnormalities (100%) in fetuses observed by ultrasonography followed by developmental delay and intellectual disability (81%), brain abnormalities (72%), facial dysmorphism (66%), hypotonia (63%), learning difficulty or language delay (50%), and seizures (47%) in pediatric and adult patients. Anti-epilepsy treatment showed the effect on controlling seizures in these patients. Cytogenomic mapping defined one proximal critical region at 6q26 containing the putative haploinsufficient gene PRKN and one distal critical region at 6q27 containing two haploinsufficient genes DLL1 and TBP. Deletions involving the PRKN gene could associate with early-onset Parkinson disease and autism spectrum disorder; deletions involving the DLL1 gene correlate with the 6q terminal deletion syndrome.Conclusion The genotype–phenotype correlations for putative haploinsufficient genes in deletions of 6q26-q27 provided evidence for precise diagnostic interpretation, genetic counseling, and clinical management of patients with a deletion of 6q26-q27.
Keywords: deletions of 6q26-q27; array comparative hybridization; haploinsufficient gene; genotype–phenotype correlations